1999
DOI: 10.4269/ajtmh.1999.60.799
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Bartonella species infecting intradomicillary animals in the Huayllacallán Valley, Ancash, Peru, a region endemic for human bartonellosis.

Abstract: Abstract. The natural cycle of Bartonella bacilliformis remains uncertain, and the suspected existence of animal reservoirs for the bacterium has never been convincingly demonstrated. We conducted a survey of Bartonella species infecting intradomicillary animals in a bartonellosis-endemic region of Peru, obtaining blood from 50 animals living in the homes of 11 families whose children had recently had bartonellosis. Bartonella-like bacteria were recovered from four of nine small rodents included in the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 35 publications
2
45
0
3
Order By: Relevance
“…berkhoffii from rodents should be low, as these Bartonella organisms have not yet been identified in any rodent reservoir (4,5,17,18,(20)(21)(22)28). Nevertheless, as B. vinsonii subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…berkhoffii from rodents should be low, as these Bartonella organisms have not yet been identified in any rodent reservoir (4,5,17,18,(20)(21)(22)28). Nevertheless, as B. vinsonii subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Various Bartonella species have been isolated from small rodents (4,5,17,18,(20)(21)(22)28). Natural coinfection of Bartonella species and Borrelia burgdorferi has also been demonstrated in wild-caught mice (22).…”
mentioning
confidence: 99%
“…Communities of rodents and insectivores in Europe (Birtles et al, 1994;Holmberg et al, 2003), Asia (Ying et al, 2002) and North and South America (Kosoy et al, 1997;Birtles et al, 1999) have all been shown to maintain bartonella infections. The overall prevalence of infections observed in SA small mammals (44 %) is similar to that reported elsewhere in the world.…”
Section: Discussionmentioning
confidence: 99%
“…These included 24 obtained from the South African (SA) rodents analysed in this study, 17 from representative strains of the Bartonella taxa with validly published names and nine from partially characterized Bartonella isolates. These nine were chosen either because they were found to share relatively high levels of sequence similarity with one or more of the sequences obtained from SA rodents (C5-rat and MR1) or because they were representatives of previously identified phylogenetic clades within the genus Bartonella; the provenance of R-phy2, C1-phy and R-phy1 has been detailed by Birtles et al (1999) and their phylogeny explored in a study by Birtles & Raoult (1996), whereas the provenance and phylogenies of SH6397GA, SH6396GA, SH6537GA and PL7238NC have been detailed by Kosoy et al (1997). The 698 bp alignment comprised 35 different sequences.…”
Section: Methodsmentioning
confidence: 99%
“…These bacteria are highly adapted to a mammalian reservoir host; further, these organisms have been shown to cause a long-lasting intraerythrocytic bacteremia in both humans and animals (11,14,22,24,25,37). Bartonella species are also the causative agents of Carrion's disease (Oroya fever and verruga peruana) (Bartonella bacilliformis) (6), trench fever (B. quintana) (11,40,43), endocarditis (B. elizabethae, B. henselae, B. vinsonii subsp. berkhoffii, B. washoensis, B. clarridgeae) (3,7,9,16,17,21,40,44), bacillary angiomatosis in immunocompromised patients (B. quintana, B. henselae) (14,30,48), neuroretinitis (B. grahamii) (28), and cat scratch disease (B. henselae, B. clarridgeiae) (5,31,42).…”
mentioning
confidence: 99%